Intercommodity price transmission and food price policies: An analysis of Ethiopian cereal markets - Rashid, Shahidur (International Food Policy Research Institute, 2011)
Cereal price variability in Ethiopia has worsened in recent years, and some of the earlier liberalizations are being reversed due to the unacceptable economic and political costs of increased price variability. The challenge now is to achieve price stability in a cost-effective way. This paper examines intercommodity price relationships to assess the relative importance of each of the three major cereals in generating price volatility. Based on the estimates from a dynamic econometric model, the paper concludes that maize is the most significant in exacerbating price variability with respect to the persistence of shocks to itself and the two other cereals. This implies that focusing on maize, instead of wheat, will not only help better stabilize prices but also reduce costs of stabilization. The results are also discussed in the context of ongoing policy discussions.